2013
DOI: 10.1021/jm400395p
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Biochemical and Structural Evaluation of Species-Specific Inhibitors against Type I Methionine Aminopeptidases

Abstract: Methionine aminopeptidases (MetAPs) are essential enzymes that make them good drug targets in cancer and microbial infections. MetAPs remove the initiator methionine from newly synthesized peptides in every living cell. MetAPs are broadly divided into type I and type II classes. Both prokaryotes and eukaryotes contain type I MetAPs, while eukaryotes have additional type II MetAP enzyme. Although several inhibitors have been reported against type I enzymes, subclass specificity is scarce. Here, using the fine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Numerous studies have shown that M. tuberculosis strains deficient in enzymes involved in various amino acid biosynthetic pathways are compromised in their ability to infect mice in comparison with the ability of parental strain (40 -42). In addition, several of these enzymes involved in amino acid biosynthesis are being currently explored for development of more potent antitubercular scaffolds (43)(44)(45)(46)(47)(48). L-Serine biosynthesis is an attractive and unexplored anti-microbial drug target because L-serine is not only involved in protein synthesis but also acts as precursor for various cellular metabolites (15, 49 -54).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that M. tuberculosis strains deficient in enzymes involved in various amino acid biosynthetic pathways are compromised in their ability to infect mice in comparison with the ability of parental strain (40 -42). In addition, several of these enzymes involved in amino acid biosynthesis are being currently explored for development of more potent antitubercular scaffolds (43)(44)(45)(46)(47)(48). L-Serine biosynthesis is an attractive and unexplored anti-microbial drug target because L-serine is not only involved in protein synthesis but also acts as precursor for various cellular metabolites (15, 49 -54).…”
Section: Discussionmentioning
confidence: 99%
“…Prokaryotes generally only generate type 1 MetAP (MetAP‐1), which can be subdivided into types 1a–d, whereas eukaryotes encode an additional enzyme, MetAP‐2, which differs by an insert of 60 amino acids . Furthermore, prokaryotes generally express either only type 1a or together with type 1c, while eukaryotes express 1b, 1d, and 2 . Drinkwater et al.…”
Section: Kinetoplastids (Trypanosomiasis and Leishmaniasis)mentioning
confidence: 99%
“…Various groups have implicated compounds consisting of biaryl ring systems capable of metal chelation as inhibitors of MetAPs from both human and bacterial sources, with the most common scaffolding including 2,2’-bipyridyl [24-28], 2-(2-pyridine)-benzimidazole [29-31] or thiabendazole [29-32] motifs. Thiabendazole ( 10 ) was crystallized with Ec MetAP1 containing three Co(II) cofactors, with the inhibitor chelating to the auxiliary Co atom closest to the entrance of the active site (Fig.…”
Section: Classes Of Metap Inhibitorsmentioning
confidence: 99%
“…Kishor reports a series of pyridinylpyrimidine based inhibitors of E. faecalis MetAP1a ( Ef MetAP1a) and Mt MetAP1c, where compounds were co-screened against Hs MetAP1b to elucidate selectivity for the bacterial forms of the enzyme [24]. The compounds are all of the general structure shown below, where a wide variety of substituents were employed at the positions indicated.…”
Section: Classes Of Metap Inhibitorsmentioning
confidence: 99%